A hidden basidiolichen rediscovered: Omphalina oreades is a separate species in the genus Lichenomphalia (Basidiomycota: Agaricales: Hygrophoraceae). (19th September 2017) - LÜCKING, Robert; THORN, R. Greg; SAAR, Irja; PIERCEY-NORMORE, Michele D.; MONCADA, Bibiana; DOERING, Jennifer; MANN, Henry; LEBEUF, Renée; VOITK, Maria; VOITK, Andrus
Abstract: Molecular studies have shown the type collection of Omphalina oreades to be conspecific with a small brown basidiolichen from the Appalachian range in Newfoundland, both with 4-spored basidia. Two sequences deposited in GenBank, originally identified as O. grisella, fell in the same clade. Sequences of the type collection of Omphalia grisella, with 2-spored basidia, formed a sister clade together with two GenBank deposits, one identified as O. grisella and the other as Omphalina velutina . Omphalina oreades is recombined here as Lichenomphalia oreades comb. nov., and the species redescribed and illustrated. Sequences of the internal transcribed spacer regions of nuclear ribosomal DNA (ITS rDNA) from the algae associated with two collections of L. oreades fell within a highly supported clade with members of an undetermined species of Coccomyxa . The most abundant algal ribosomal large subunit sequence from granules at the base of a different collection matched GenBank sequences identified as Chloroidium ellipsoideum, which is probably either a free-living algal species or a partner to a species of Trapeliopsis. The second most abundant sequence matched Coccomyxa subellipsoidea and is the most likely photobiont of L. oreades . Further studies are required to elucidate the relationship of L. velutina to these taxa.